Anti-colonial methodologies and practices for settler colonial studies. (2nd October 2017) - Carlson, Elizabeth
ABSTRACT: Indigenous scholars have called on settler people to engage in processes of decolonization. To investigate how white settler individuals living on Indigenous lands occupied by the Canadian state are responding to that call, it was necessary to articulate a comprehensive research approach that centralizes Indigenous sovereignty and disrupts colonial research dynamics. This article focuses on the articulation, grounding, and deployment of an anti-colonial research methodology by a white settler scholar. Though developed in the context of a specific project, this approach has much wider relevance and application possibilities. I demonstrate the values and practices of the anti-colonial research methodology to academia generally and settler colonial studies specifically.